Junk drawer engineering : 25 construction challenges that don't cost a thing - Mercer, Bobby, 1961- (Chicago Review Press, 2017)
"Children love challenges, especially ones that involve hands-on experimentation and friendly competition. Can they build a bridge using only pasta and glue, one that a toy car can drive both under and over, and is sturdy enough to carry a considerable weight? Can they construct a "roller coaster" from recycled cardboard tubes in which the marble "car" jumps a track to land safely at its final destination? And can they create a device to safely catch a freefalling egg? These projects and more can be found in Junk Drawer Engineering, which demonstrates that you don't need high-tech equipment to make learning fun--just what you can find in your recycling bin and around the house. At its heart, engineering is the application of science to solve a design problem. Science teacher Bobby Mercer provides readers with 25 open-ended design challenges for children of all ages. The projects can be modified to meet the skill levels of the children doing them, from elementary school kids to teenagers. Though each challenge includes suggested materials and one step-by-step, illustrated solution, children are encouraged to modify and improve on the basic design, and come up with new and more complicated design parameters. Educators and parents will find this title a handy resource to teach children problem-solving skills and applied physics, all while having a lot of fun."--